Laminate, packaging film and method for manufacturing laminate

By using a heat sealing layer containing a resin component of 4-methyl-1-pentene and an α-olefin copolymer in the laminate of the film, the problem of the conventional film being reduced when the heat sealing property is improved, and the effect of excellent breathability and heat sealing property is achieved.

CN119654237AActive Publication Date: 2025-03-18MITSUI CHEMICALS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380058398.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-25
Publication Date
2025-03-18
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

When the existing film improves heat sealing, the breathability is easily reduced, and it is difficult to meet the excellent requirements of both.

Method used

A laminated body with a base material and a heat sealing layer sequentially to the thickness direction is used. The heat sealing layer is composed of a resin component composed of 4-methyl-1-pentene, an α-olefin copolymer having 2 or more carbon atoms or less, or a modified product thereof, ensuring excellent heat sealing and breathability.

Benefits of technology

A laminated body and packaging film with excellent breathability and heat sealing properties are realized, and the problem of difficulty in improving breathability and heat sealing properties in the prior art is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654237A_ABST
    Figure CN119654237A_ABST
Patent Text Reader

Abstract

A laminate (1) is provided with a substrate (2) and a heat sealing layer (3). The heat sealing layer (3) is a dried product of a coating composition. The coating composition contains a resin component comprising a copolymer of 4-methyl-1-pentene and an alpha-olefin (excluding 4-methyl-1-pentene) and / or a modified product of the copolymer. In the copolymer, the content ratio of structural units derived from 4-methyl-1-pentene is 50 mol% or more and 99 mol% or less, and the content ratio of structural units derived from alpha-olefin is 1 mol% or more and 50 mol% or less, with respect to the total amount of structural units derived from 4-methyl-1-pentene and structural units derived from alpha-olefin. The oxygen permeation coefficient and the carbon dioxide permeation coefficient of the laminate are 1000 cm < 3 >. Mm / (m < 2 >. 24 hr. Atm) or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate, a packaging film, and a method for producing the laminate, and more particularly to a laminate, a packaging film having the laminate, and a method for producing the laminate. Background Art

[0002] Conventionally, it is known that films formed of copolymers containing structural units derived from 4-methyl-1-pentene have excellent air permeability. Therefore, such films can be suitably used as packaging materials for fresh foods, for example.

[0003] As such a film, for example, a film obtained by casting a resin composition comprising a thermoplastic resin (A) and a thermoplastic resin (B) other than the thermoplastic resin (A), wherein the thermoplastic resin (A) is a copolymer comprising a structural unit derived from 4-methyl-1-pentene and a structural unit derived from an α-olefin having a carbon number of 2 to 20, and the thermoplastic resin (B) is an olefin copolymer (for example, see Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-121322 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, the film is required to have air permeability and heat sealability.

[0009] In Patent Document 1, a polymer other than a polymer containing a structural unit derived from 4-methyl-1-pentene (specifically, a thermoplastic resin (B)) is blended from the viewpoint of improving heat sealing properties. However, blending of the thermoplastic resin (B) has the disadvantage of reducing air permeability.

[0010] The present invention provides a laminate having excellent air permeability and heat sealing properties, a packaging film including the laminate, and a method for producing the laminate.

[0011] Means for solving problems

[0012] The present invention [1] is a laminated body comprising a substrate and a heat sealant layer in this order on one side in a thickness direction, wherein the heat sealant layer is a dried product of a coating composition, wherein the coating composition comprises a resin component, wherein the resin component comprises a copolymer of 4-methyl-1-pentene and an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene), and / or a modified product of the copolymer, wherein in the copolymer, the content of the structural unit derived from the 4-methyl-1-pentene is 50 mol% to 99 mol%, and the content of the structural unit derived from the α-olefin is 1 mol% to 50 mol%, relative to the total amount of the structural unit derived from the 4-methyl-1-pentene and the structural unit derived from the α-olefin, and the oxygen permeability coefficient and the carbon dioxide permeability coefficient of the laminated body are 1000 cm 3 mm / (m 2 ·24hr·atm) or more.

[0013] The present invention [2] includes the laminate according to the above [1], wherein the substrate is an air-permeable porous substrate or a substrate formed of a polymer of 4-methyl-1-pentene.

[0014] The present invention [3] includes the laminate according to [1] or [2], wherein the thickness of the heat sealant layer is 1 μm or more and less than 50 μm.

[0015] The present invention [4] includes the laminate according to any one of [1] to [3] above, wherein the peel strength measured by the following test is 2.0 N / 15 mm or more.

[0016] Test: Two laminates were prepared. The two laminates were bonded together so that their heat-sealed layers were in contact with each other, and heat-sealed at 160°C, 0.3 MPa, and 2 seconds to produce a film. The film was peeled off in a direction 180° relative to the heat-sealed surface at a tensile speed of 50 mm / min and a temperature of 23°C, and the peel strength was measured.

[0017] The present invention [5] includes a packaging film comprising the laminate according to any one of [1] to [4] above.

[0018] The present invention [6] includes a method for producing a laminate according to any one of [1] to [4] above, the method comprising the following steps: a first step of preparing the substrate; a second step of dissolving the coating composition in an organic solvent to prepare a varnish; and a third step of applying the varnish to one surface of the substrate in the thickness direction and drying the varnish to thereby configure a heat sealing layer.

[0019] Effects of the Invention

[0020] In the laminate of the present invention, the heat sealant layer is a dried product of the coating composition and therefore has excellent heat sealability.

[0021] In addition, in the laminate, the coating composition includes a resin component composed of a copolymer of 4-methyl-1-pentene and an α-olefin having a carbon number of 2 to 20 (excluding 4-methyl-1-pentene) and / or a modified product of the copolymer. Therefore, air permeability can be improved.

[0022] The packaging film of the present invention comprises the laminate of the present invention and therefore has excellent air permeability and heat sealing properties.

[0023] The manufacturing method of the laminate of the present invention comprises the following steps: a second step of dissolving the coating composition in an organic solvent to prepare a varnish; and a third step of applying the varnish to one surface in the thickness direction of the substrate and drying it to configure a heat-sealing layer. That is, through the second step and the third step, a heat-sealing layer as a dried product of the coating composition can be configured on one surface in the thickness direction of the substrate. Therefore, according to this method, a laminate with excellent heat-sealing properties can be manufactured.

[0024] In addition, in the manufacturing method of the laminate, a coating composition containing a resin component composed of a copolymer of 4-methyl-1-pentene and an α-olefin having a carbon number of 2 to 20 (excluding 4-methyl-1-pentene) and / or a modified product of the copolymer is used. Therefore, according to this method, a laminate having excellent air permeability can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] [ Figure 1 ] Figure 1 This is a schematic diagram showing one embodiment of the laminated body of the present invention.

[0026] [ Figure 2 ] Figure 2 This is a schematic diagram showing one embodiment of the method for producing a laminated body of the present invention. Figure 2 A shows the first step, namely, preparing the substrate 2 . Figure 2 B shows the third step, that is, applying a varnish of the coating composition on one surface in the thickness direction of the substrate and drying it, thereby arranging a heat seal layer on one surface in the thickness direction of the substrate. DETAILED DESCRIPTION

[0027] <Laminate>

[0028] Reference Figure 1 , one embodiment of the laminated body of the present invention is described in detail.

[0029] Figure 1In the figure, the up-down direction of the paper is the up-down direction (thickness direction). In addition, the upper side of the paper is the upper side (one side in the thickness direction). In addition, the lower side of the paper is the lower side (the other side in the thickness direction). In addition, the left-right direction and the depth direction of the paper are the surface directions orthogonal to the up-down direction. Specifically, according to the direction arrows of each figure.

[0030] The laminate 1 has a film shape (including a sheet shape) having a predetermined thickness. The laminate 1 extends along a plane direction perpendicular to the thickness direction.

[0031] like Figure 1 As shown, the laminate 1 includes a substrate 2 and a heat sealant layer 3 in this order on one side in the thickness direction.

[0032] Specifically, the laminate 1 includes a substrate 2 and a heat sealant layer 3 disposed on the upper surface (one surface in the thickness direction) of the substrate 2 .

[0033] The thickness of the laminated body 1 is, for example, not less than 5 μm, and, for example, not more than 10000 μm.

[0034] <Base Material>

[0035] The substrate 2 extends in a plane direction (a direction perpendicular to the thickness direction) and has a sheet shape having a front surface and a back surface.

[0036] The substrate 2 is preferably selected so that the air permeability described below becomes equal to or greater than a predetermined value.

[0037] Examples of such a substrate 2 include an air-permeable porous substrate and a substrate formed of a polymer of 4-methyl-1-pentene (preferably a homopolymer of 4-methyl-1-pentene).

[0038] As the air-permeable porous substrate, for example, paper, cloth, knitted fabric, and nonwoven fabric can be cited. Specifically, such a porous substrate is composed of, for example, polyolefin, polyester, natural fiber represented by cellulose, fluorine-based resin, silicone-based resin, and urethane-based resin.

[0039] As the substrate 2, a permeable porous substrate is preferably used. If the substrate 2 is a permeable porous substrate, the dried product of the coating composition (described later) can penetrate into the substrate 2, and the anchoring effect caused by this can improve the adhesion between the substrate 2 and the heat sealing layer 3. As a result, the heat sealing property is improved.

[0040] The thickness of the substrate 2 is, for example, not less than 1 μm, and, for example, not more than 9999 μm.

[0041] <Heat sealing layer>

[0042] The heat sealant layer 3 extends in the plane direction (direction perpendicular to the thickness direction) and has a sheet shape having a flat front surface and a flat back surface. The heat sealant layer 3 is in contact with one surface of the substrate 2 in the thickness direction.

[0043] The heat seal layer 3 is a dried product of the coating composition and therefore has excellent heat sealability.

[0044] The coating composition includes a resin component.

[0045] [Resin component]

[0046] The resin component is composed of a copolymer of 4-methyl-1-pentene and an α-olefin having a carbon number of 2 to 20 (excluding 4-methyl-1-pentene) (hereinafter, sometimes referred to as a copolymer of 4-methyl-1-pentene and an α-olefin), and / or a modified product of the copolymer of 4-methyl-1-pentene and an α-olefin. In other words, the resin component substantially contains only the copolymer of 4-methyl-1-pentene and an α-olefin, and / or a modified product of the copolymer of 4-methyl-1-pentene and an α-olefin. The resin component substantially containing only the copolymer of 4-methyl-1-pentene and α-olefin and / or the modified copolymer of 4-methyl-1-pentene and α-olefin means that the content ratio of the copolymer of 4-methyl-1-pentene and α-olefin and / or the modified copolymer of 4-methyl-1-pentene and α-olefin relative to the resin component is, for example, 95% by mass or more, preferably 99% by mass or more, more preferably 99.9% by mass or more, and further preferably 100% by mass.

[0047] When the resin component is composed of a copolymer of 4-methyl-1-pentene and an α-olefin and / or a modified product of a copolymer of 4-methyl-1-pentene and an α-olefin, air permeability can be improved.

[0048] (Copolymer of 4-methyl-1-pentene and α-olefin)

[0049] The copolymer of 4-methyl-1-pentene and an α-olefin is a polymerization product of 4-methyl-1-pentene and an α-olefin having 2 to 20 carbon atoms.

[0050] Examples of the α-olefin having 2 to 20 carbon atoms include linear α-olefin having 2 to 20 carbon atoms and branched α-olefin having 2 to 20 carbon atoms.

[0051] Examples of the linear α-olefin having 2 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0052] Examples of the branched α-olefin having a carbon number of 2 to 20 include 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4,4-dimethyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene.

[0053] As the α-olefin having 2 to 20 carbon atoms, preferably, a linear α-olefin having 2 to 20 carbon atoms can be mentioned. As the α-olefin having 2 to 20 carbon atoms, more preferably, a linear α-olefin having 2 to 4 carbon atoms can be mentioned. As the α-olefin having 2 to 20 carbon atoms, more preferably, propylene can be mentioned.

[0054] The α-olefins having 2 to 20 carbon atoms may be used alone or in combination of two or more.

[0055] Furthermore, the copolymer of 4-methyl-1-pentene and an α-olefin can be obtained by polymerizing 4-methyl-1-pentene and an α-olefin having a carbon number of 2 to 20 based on the method described in International Publication No. 2004 / 87775. Specifically, the copolymer of 4-methyl-1-pentene and an α-olefin can be obtained by polymerizing 4-methyl-1-pentene and an α-olefin having a carbon number of 2 to 20 in the presence of a metallocene catalyst.

[0056] Thereby, a copolymer of 4-methyl-1-pentene and an α-olefin (a reaction liquid containing a copolymer of 4-methyl-1-pentene and an α-olefin) can be obtained.

[0057] In the copolymer of 4-methyl-1-pentene and an α-olefin, the content ratio of the structural unit derived from 4-methyl-1-pentene is 50 mol% or more, preferably 60 mol% or more, and is 99 mol% or less, preferably 90 mol% or less, relative to the total amount of the structural unit derived from 4-methyl-1-pentene and the structural unit derived from the α-olefin.

[0058] When the content ratio of the structural unit derived from 4-methyl-1-pentene is not less than the above lower limit, air permeability can be improved.

[0059] On the other hand, when the content ratio of the structural unit derived from 4-methyl-1-pentene is less than the above lower limit, the air permeability decreases.

[0060] Moreover, when the content ratio of the structural unit derived from 4-methyl-1-pentene is below the above upper limit, the heat sealing property and the film-forming property can be improved.

[0061] On the other hand, when the content ratio of the structural unit derived from 4-methyl-1-pentene exceeds the above upper limit, the heat sealing property and the film-forming property are deteriorated.

[0062] The content of the structural unit derived from α-olefin is 1 mol% or more, preferably 10 mol% or more, and 50 mol% or less, preferably 40 mol% or less, based on the total amount of the structural unit derived from 4-methyl-1-pentene and the structural unit derived from α-olefin.

[0063] When the content of the structural unit derived from an α-olefin is not less than the above lower limit, heat sealing properties and film-forming properties can be improved.

[0064] On the other hand, when the content of the structural unit derived from the α-olefin is less than the above lower limit, the heat sealing property and the film-forming property are deteriorated.

[0065] Moreover, when the structural unit derived from an α-olefin is equal to or less than the above upper limit, air permeability can be improved.

[0066] On the other hand, when the content of the structural unit derived from the α-olefin exceeds the above upper limit, the air permeability decreases.

[0067] It should be noted that the content ratio of the structural unit derived from 4-methyl-1-pentene and the content ratio of the structural unit derived from α-olefin can be determined, for example, 13 The results can be confirmed by known means such as C-NMR measurement.

[0068] The weight average molecular weight of the copolymer of 4-methyl-1-pentene and α-olefin measured by GPC (gel permeation chromatography) and converted to standard polystyrene is, for example, 10,000 or more, preferably 50,000 or more, more preferably 100,000 or more, further preferably 300,000 or more, and, for example, 500,000 or less, preferably 400,000 or less.

[0069] The weight average molecular weight / number average molecular weight (Mw / Mn) of the copolymer of 4-methyl-1-pentene and an α-olefin is, for example, 1.5 or more, preferably 2.0 or more, and, for example, 4.0 or less, preferably 3.0 or less.

[0070] The melting point of the copolymer of 4-methyl-1-pentene and an α-olefin is not observed, or, when the melting point is observed, the melting point is, for example, 199°C or less, preferably 150°C or less, more preferably 140°C or less, and for example, 80°C or more, preferably 100°C or more.

[0071] When the melting point of the copolymer of 4-methyl-1-pentene and an α-olefin is not observed or the melting point is equal to or lower than the above upper limit, the heat sealability can be further improved.

[0072] It should be noted that the melting point can be measured using a differential scanning calorimeter (hereinafter the same). In addition, the so-called unobservable melting point means that in the measurement based on the differential scanning calorimeter, a crystal melting peak with a crystal melting heat of 1 J / g or more is not observed in the range of -150°C to 200°C.

[0073] (Modified copolymer of 4-methyl-1-pentene and α-olefin)

[0074] The modified product of the copolymer of 4-methyl-1-pentene and α-olefin (hereinafter, sometimes referred to as a modified product) can be obtained by graft-modifying the copolymer of 4-methyl-1-pentene and α-olefin with a graft component.

[0075] As the graft component, for example, ethylenically unsaturated compounds containing a hydroxyl group, ethylenically unsaturated compounds containing an amino group, unsaturated carboxylic acids, unsaturated carboxylic anhydrides, vinyl ester compounds, and ethylenically unsaturated compounds containing a thiol group can be cited. As the graft component, preferably, unsaturated carboxylic acids and / or unsaturated carboxylic anhydrides can be cited.

[0076] Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, norbornene dicarboxylic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid.

[0077] Examples of the unsaturated carboxylic anhydride include maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride.

[0078] As the graft component, unsaturated carboxylic acid anhydride is more preferred. As the graft component, maleic anhydride is further preferred.

[0079] The graft components may be used alone or in combination of two or more.

[0080] Furthermore, the modified product can be obtained by graft-modifying a copolymer of 4-methyl-1-pentene and an α-olefin with a graft component.

[0081] In order to graft-modify the copolymer of 4-methyl-1-pentene and α-olefin with a graft component, for example, first, the copolymer of 4-methyl-1-pentene and α-olefin is dissolved in a known organic solvent (e.g., toluene), then the graft component and a radical polymerization initiator are added, mixed, and heated (specifically, melt-mixed).

[0082] The modification amount (introduction amount) of the graft component in the modified product of the copolymer of 4-methyl-1-pentene and α-olefin, that is, the content ratio of the structural unit derived from the graft component in the modified product of the copolymer of 4-methyl-1-pentene and α-olefin, is, for example, 0.1 mass % or more, preferably 0.5 mass % or more, and is, for example, 10 mass % or less, preferably 5.0 mass % or less, more preferably 3.0 mass % or less, and further preferably 2.0 mass % or less.

[0083] The above modification amount can be determined by, for example 1 The results can be confirmed by known means such as H-NMR measurement.

[0084] Examples of the radical polymerization initiator include organic peroxides and organic peresters.

[0085] Examples of the organic peroxide include dicumyl peroxide, benzoyl peroxide, dichlorobenzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(peroxybenzoate)hex-3-yne, 1,4-bis(tert-butylperoxyisopropyl)benzene, lauroyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl peroxybenzoate, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane. Examples of the organic perester include tert-butyl peroxyacetate, tert-butyl peroxyphenylacetate, tert-butyl peroxyisobutyrate, tert-butyl peroxysec-octanoate, tert-butyl peroxypivalate, cumyl peroxypivalate, and tert-butyl peroxydiethylacetate.

[0086] As the radical polymerization initiator, preferably, an organic peroxide is used. As the radical polymerization initiator, more preferably, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane is used.

[0087] The blending ratio of the radical polymerization initiator is, for example, 0.001 parts by mass or more, and for example, 10 parts by mass or less, relative to 100 parts by mass of the copolymer of 4-methyl-1-pentene and α-olefin.

[0088] The radical polymerization initiator can be used alone or in combination of two or more.

[0089] The heating temperature is, for example, 50° C. or higher, preferably 80° C. or higher, and for example, 250° C. or lower. The reaction time is, for example, 1 minute or longer, and for example, 10 hours or shorter.

[0090] Thus, the copolymer of 4-methyl-1-pentene and α-olefin is graft-modified with the graft component, thereby obtaining a modified product of the copolymer of 4-methyl-1-pentene and α-olefin (varnish of the modified product).

[0091] The weight average molecular weight of the modified product measured by GPC (gel permeation chromatography) and converted to standard polystyrene is, for example, 10,000 or more, preferably 50,000 or more, more preferably 100,000 or more, further preferably 200,000 or more, and, for example, 500,000 or less, preferably 300,000 or less.

[0092] The weight average molecular weight / number average molecular weight (Mw / Mn) of the modified product is, for example, 1.5 or more, preferably 1.9 or more, and, for example, 4.0 or less, preferably 3.0 or less.

[0093] The melting point of the modified product is not observed, or, when the melting point is observed, the melting point is, for example, 199°C or less, preferably 150°C or less, more preferably 140°C or less, and for example, 80°C or more, preferably 100°C or more.

[0094] When the melting point of the modified product is not observed, or the melting point is equal to or lower than the above upper limit, the heat sealing property can be further improved.

[0095] As described above, the resin component is composed of a copolymer of 4-methyl-1-pentene and an α-olefin and / or a modified product of a copolymer of 4-methyl-1-pentene and an α-olefin. The resin component preferably does not contain a modified product of a copolymer of 4-methyl-1-pentene and an α-olefin but is composed of a copolymer of 4-methyl-1-pentene and an α-olefin, or does not contain a copolymer of 4-methyl-1-pentene and an α-olefin but is composed of a modified product of a copolymer of 4-methyl-1-pentene and an α-olefin.

[0096] In addition, since the resin component is composed of a copolymer of 4-methyl-1-pentene and an α-olefin and / or a modified product of a copolymer of 4-methyl-1-pentene and an α-olefin, the resin component does not substantially contain other thermoplastic resins. The so-called resin component does not substantially contain other thermoplastic resins means that the content ratio of other thermoplastic resins relative to the resin component is, for example, 5% by mass or less, preferably 1% by mass or less, more preferably 0.1% by mass or less, and further preferably 0% by mass.

[0097] As other thermoplastic resins, for example, thermoplastic resin (B) described in JP-A-2016-121322 can be cited. Specifically, as other thermoplastic resins, olefin polymers (polymers of α-olefins (excluding 4-methyl-1-pentene)) can be cited.

[0098] When the resin component does not substantially contain other thermoplastic resins, air permeability can be improved.

[0099] The content ratio of the resin component with respect to the coating composition is, for example, 80 mass % or more, preferably 90 mass % or more, more preferably 95 mass % or more, and, for example, 100 mass % or less.

[0100] [additive]

[0101] The coating composition may contain additives in appropriate proportions as required.

[0102] Examples of the additives include leveling agents, defoaming agents, antioxidants, heat stabilizers, ultraviolet absorbers, plasticizers, surfactants, pigments, thixotropic agents, thickeners, tackifiers, surface conditioners, anti-settling agents, weathering agents, pigment dispersants, antistatic agents, fillers, mildew-proof agents, and silane coupling agents.

[0103] The additives may be used alone or in combination of two or more.

[0104] [Preparation of coating composition]

[0105] The coating composition can be prepared by mixing the resin component and additives added as necessary.

[0106] In the second step described below, the coating composition is dissolved in an organic solvent (described below) to prepare a varnish of the coating composition. The varnish of the coating composition is an organic solvent solution of the coating composition.

[0107] Next, although it will be described in detail later, the heat seal layer 3 can be formed by applying a varnish of a coating composition on one surface in the thickness direction of the substrate 2 and drying it.

[0108] The thickness of the heat seal layer 3 is, for example, 1 μm or more, preferably 3 μm or more, from the viewpoint of molding processability, and is, for example, less than 50 μm, preferably less than 20 μm, and more preferably 19 μm or less, from the viewpoint of improving heat sealability.

[0109] <Method for producing laminate>

[0110] Reference Figure 2 A and Figure 2 B. One embodiment of a method for producing a laminate is described.

[0111] The manufacturing method of the laminate 1 comprises the following steps: a first step of preparing a substrate 2; a second step of dissolving a coating composition in an organic solvent to prepare a varnish of the coating composition; and a third step of applying the varnish of the coating composition to one surface in the thickness direction of the substrate 2 and drying it, thereby configuring a heat sealing layer 3 on one surface in the thickness direction of the substrate 2.

[0112] [1st step]

[0113] In the first step, if Figure 2 As shown in A, a substrate 2 is prepared.

[0114] [Step 2]

[0115] In the second step, the coating composition is dissolved in an organic solvent to prepare a varnish of the coating composition.

[0116] As organic solvents, for example, aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, ketones, alkyl esters, glycol ether esters, ethers and polar aprotic solvents can be cited. As aliphatic hydrocarbons, for example, n-hexane, n-heptane and octane can be cited. As alicyclic hydrocarbons, for example, cyclohexane and methylcyclohexane can be cited. As aromatic hydrocarbons, for example, toluene and xylene can be cited. As ketones, for example, acetone, methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone can be cited. As alkyl esters, for example, methyl acetate, ethyl acetate, butyl acetate and isobutyl acetate can be cited. As glycol ether esters, for example, methyl cellosolve acetate, ethyl cellosolve acetate, methyl carbitol acetate, ethyl carbitol acetate, ethylene glycol ethyl ether acetate, propylene glycol methyl ether acetate, 3-methyl-3-methoxybutyl acetate and ethyl 3-ethoxypropionate can be cited. Examples of the ethers include diethyl ether, tetrahydrofuran, and dioxane, and examples of the polar aprotic compounds include N-methylpyrrolidone, dimethylformamide, N,N'-dimethylacetamide, dimethyl sulfoxide, and hexamethylphosphoramide.

[0117] As the organic solvent, preferably, alicyclic hydrocarbons and / or alkyl esters are used. As the solvent, more preferably, methylcyclohexane and / or ethyl acetate are used.

[0118] The organic solvent may be used alone or in combination of two or more. Preferably, methylcyclohexane and ethyl acetate are used in combination as the solvent.

[0119] The mixing ratio of the organic solvent relative to 100 parts by mass of the resin component is, for example, 200 parts by mass or more, and for example, 1000 parts by mass or less.

[0120] The solid content concentration of the varnish of the coating composition is, for example, 5 mass % or more, and for example, 70 mass % or less.

[0121] [Step 3]

[0122] In the third step, if Figure 2 As shown in B, a varnish of a coating composition is applied to one surface of the substrate 2 in the thickness direction and dried, thereby providing a heat sealant layer 3 on one surface of the substrate 2 in the thickness direction.

[0123] In order to apply the varnish of the coating composition to one surface in the thickness direction of the substrate 2 , first, the one surface in the thickness direction of the substrate 2 is subjected to a surface treatment as necessary.

[0124] Examples of the surface treatment include corona treatment, plasma treatment, flame treatment, ozone treatment, primer treatment, glow treatment, and saponification treatment, and preferably, corona treatment is used.

[0125] Next, the coating composition is applied to one surface of the substrate 2 in the thickness direction by a known method, and is dried by heating as necessary.

[0126] The heating temperature is, for example, 50° C. or higher, preferably 80° C. or higher, and, for example, 250° C. or lower. The heating time is, for example, 10 seconds or higher, and, for example, 600 seconds or lower.

[0127] In addition, especially when the substrate 2 is a non-woven fabric, after applying the coating composition to one surface in the thickness direction of the substrate 2, from the viewpoint of allowing the coating composition to penetrate into the non-woven fabric, it is allowed to stand for, for example, 1 hour, and for example, less than 50 hours, and then heated and dried as needed.

[0128] Thus, the heat sealant layer 3 which is a dried product of the varnish of the coating composition (ie, a dried product of the coating composition) is arranged (formed) on one surface in the thickness direction of the substrate 2. In the above manner, the laminate 1 is manufactured.

[0129] Furthermore, as described above, such a laminate 1 includes the heat sealant layer 3 which is a dried product of the coating composition, and therefore has excellent heat sealability.

[0130] Specifically, in the laminate 1 , the peel strength measured by the following test is, for example, 2.0 N / 15 mm or more, or preferably 4.0 N / 15 mm or more.

[0131] In the test, first, two laminates 1 were prepared. Then, the two laminates 1 were attached so that their heat seal layers 3 were in contact with each other, and heat-sealed at 160°C, 0.3 MPa, and 2 seconds to produce a film. The film was peeled off in a direction of 180° relative to the heat-sealed surface at a tensile speed of 50 mm / min and a temperature of 23°C, and the peel strength was measured.

[0132] The oxygen permeability coefficient and carbon dioxide permeability coefficient of the laminate 1 are 1000 cm 3 mm / (m 2 ·24hr·atm) or more.

[0133] More specifically, the oxygen permeability coefficient is 1000 cm 3 mm / (m 2 ·24hr·atm) or more, preferably 1400cm 3 mm / (m 2 ·24hr·atm) or more, and for example, 100000cm 3 mm / (m 2 ·24hr·atm) or less.

[0134] In addition, the carbon dioxide permeability coefficient is 1000cm 3 mm / (m 2 ·24hr·atm) or more, preferably 2000cm 3 mm / (m 2 ·24hr·atm) or more, more preferably 4000cm 3 mm / (m 2 ·24hr·atm) or more, and for example, 200000cm 3 mm / (m 2 ·24hr·atm) or less.

[0135] In addition, the measurement method of the oxygen permeability coefficient and the carbon dioxide permeability coefficient is described in detail in the examples described later.

[0136] Furthermore, since such a laminate 1 is excellent in air permeability and heat sealing property, it can be particularly suitably used as a packaging film. Such a packaging film includes the laminate 1. Therefore, it is excellent in air permeability and heat sealing property.

[0137] <Effects>

[0138] In the laminate 1, the coating composition contains a resin component composed of a copolymer of 4-methyl-1-pentene and an α-olefin and / or a modified product of a copolymer of 4-methyl-1-pentene and an α-olefin, so that air permeability can be improved.

[0139] Specifically, in Patent Document 1, from the viewpoint of improving heat sealing properties, a polymer other than a polymer containing a structural unit derived from 4-methyl-1-pentene (specifically, a thermoplastic resin (B)) is blended into a thermoplastic resin (A). However, when the thermoplastic resin (B) is blended, there is a disadvantage that air permeability decreases.

[0140] On the other hand, in the laminate 1, the resin component is composed of a copolymer of 4-methyl-1-pentene and an α-olefin and / or a modified product of a copolymer of 4-methyl-1-pentene and an α-olefin. Therefore, the resin component does not substantially contain other thermoplastic resins (specifically, the thermoplastic resin (B) of Patent Document 1).

[0141] Therefore, it is possible to suppress a decrease in air permeability due to the addition of the thermoplastic resin (B).

[0142] As a result, air permeability can be improved.

[0143] In addition, in the laminate 1, the heat seal layer 3 is a dried product of the coating composition. Therefore, the heat sealability is excellent. Specifically, in the laminate 1, even when the substrate 2 is an air-permeable porous substrate (preferably paper and nonwoven fabric) and has unevenness on its surface, the thickness of the heat seal layer 3 can be reduced (for example, less than 50 μm), and the heat sealability can be improved.

[0144] Example

[0145] Next, the present invention is described based on examples and comparative examples, but the present invention is not limited to the following examples. It should be noted that, unless otherwise specified, "parts" and "%" are based on mass. In addition, the specific numerical values ​​of the mixing ratio (containing ratio), physical property values, parameters, etc. used in the following description can be replaced by the upper limit value (numerical value defined in the form of "below", "less than") or the lower limit value (numerical value defined in the form of "above", "greater than") of the corresponding mixing ratio (containing ratio), physical property values, parameters, etc. recorded in the above-mentioned "specific implementation method".

[0146] <Details of ingredients>

[0147] The trade names and abbreviations of the components used in each Production Example, each Example, and each Comparative Example are described in detail.

[0148] Paper: Trade name "OK Blizzard", manufactured by Oji Materia Co., Ltd.

[0149] Nonwoven fabric: Product name "Syntex PK102", manufactured by Mitsui Chemicals, Inc.

[0150] TPX: A membrane formed of a polymer of 4-methyl-1-pentene, trade name "Opulent XP-88B", manufactured by Mitsui Chemicals Tohcello, Inc.

[0151] Propylene·ethylene random copolymer: Prime Polypro (registered trademark) F327, propylene·ethylene random copolymer, manufactured by Prime Polymer Co., Ltd.

[0152] <Production of Copolymer of 4-Methyl-1-pentene and Propylene>

[0153] Production Example 1

[0154] In a SUS autoclave (1.5 L capacity) equipped with a stirring blade and fully purged with nitrogen, 300 ml of n-hexane (dried on activated alumina under a dry nitrogen atmosphere) and 450 ml of 4-methyl-1-pentene were added at 23° C. Next, 0.75 ml of a toluene solution of 1.0 mmol / ml triisobutylaluminum (TIBAL) was added to the autoclave and stirred.

[0155] Next, the autoclave was heated to an internal temperature of 60° C. and pressurized with propylene so that the total pressure (gauge pressure) became 0.40 MPa.

[0156] Next, 0.34 ml of a toluene solution containing 1 mmol of methylaluminoxane in terms of Al and 0.01 mmol of diphenylmethylene (1-ethyl-3-tert-butyl-cyclopentadienyl) (2,7-di-tert-butyl-fluorenyl) zirconium dichloride prepared in advance was injected into the autoclave using nitrogen to start a polymerization reaction. During the polymerization reaction, the temperature was adjusted so that the internal temperature of the autoclave was 60° C.

[0157] 60 minutes after the start of the polymerization, 5 ml of methanol was pressurized into the autoclave using nitrogen to stop the polymerization reaction, and then the pressure in the autoclave was reduced to atmospheric pressure. After the pressure reduction, acetone was added to the reaction solution while stirring the reaction solution. Thus, a reaction solution containing a copolymer of 4-methyl-1-pentene and propylene was obtained.

[0158] Next, the reaction liquid containing the copolymer of 4-methyl-1-pentene and propylene was dried under reduced pressure at 100° C. for 12 hours to obtain 36.9 g of a powdery copolymer of 4-methyl-1-pentene and propylene.

[0159] The weight average molecular weight of the copolymer was 337,000. In addition, the weight average molecular weight / number average molecular weight (Mw / Mn) of the copolymer was 2.1. In addition, the melting point of the copolymer was not observed. In addition, in the copolymer, relative to the total amount of the structural units derived from 4-methyl-1-pentene and the structural units derived from propylene, the content ratio of the structural units derived from 4-methyl-1-pentene was 73 mol%, and the content ratio of the structural units derived from propylene was 27 mol%. It should be noted that the above content ratio is obtained by 13Measured by C-NMR measurement.

[0160] Production Example 2

[0161] 44.0 g of a powdery copolymer of 4-methyl-1-pentene and propylene was obtained by the same procedure as in Production Example 1. However, in Production Example 2, the mixture was pressurized with propylene so that the total pressure (gauge pressure) became 0.19 MPa.

[0162] The weight average molecular weight of the copolymer was 340,000. In addition, the weight average molecular weight / number average molecular weight (Mw / Mn) of the copolymer was 2.1. In addition, the melting point of the copolymer was 132°C. In addition, in the copolymer, the content ratio of the structural unit derived from 4-methyl-1-pentene was 85 mol%, and the content ratio of the structural unit derived from propylene was 15 mol%, relative to the total amount of the structural unit derived from 4-methyl-1-pentene and the structural unit derived from propylene. It should be noted that the above content ratio is obtained by 13 Measured by C-NMR measurement.

[0163] <Production of Maleic Anhydride-Modified Copolymer of 4-Methyl-1-Pentene and Propylene> Production Example 3

[0164] The copolymer of 4-methyl-1-pentene and propylene of Production Example 1 was charged from the resin charging part of the twin-screw kneading extruder with a vent. Furthermore, 2 parts by mass of maleic anhydride as a graft component and 0.4 parts by mass of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane as a radical polymerization initiator were added to 100 parts by mass of the copolymer of 4-methyl-1-pentene and propylene.

[0165] Next, the copolymer of 4-methyl-1-pentene and propylene, the graft component, and the radical polymerization initiator are melt-kneaded at 190° C. Then, the kneaded product is discharged from the kneading extruder and cooled. After cooling, the product is pelletized using a pelletizer. Thus, a maleic anhydride-modified product of the copolymer of 4-methyl-1-pentene and propylene is obtained.

[0166] The weight average molecular weight of the modified product was 231000. In addition, the weight average molecular weight / number average molecular weight (Mw / Mn) of the modified product was 2.0. In addition, the melting point of the modified product could not be observed. In addition, the modification amount (introduction amount) of the graft component in the maleic anhydride modified product of the copolymer of 4-methyl-1-pentene and propylene was 0.9 mass %. It should be noted that the above modification amount is obtained by 1 Measured by H-NMR measurement.

[0167] Production Example 4

[0168] A maleic anhydride-modified copolymer of 4-methyl-1-pentene and propylene was obtained by the same procedure as in Production Example 3. However, in Production Example 4, the copolymer of 4-methyl-1-pentene and propylene of Production Example 2 was used instead of the copolymer of 4-methyl-1-pentene and propylene of Production Example 1.

[0169] The weight average molecular weight of the modified product was 208000. In addition, the weight average molecular weight / number average molecular weight (Mw / Mn) of the modified product was 2.1. In addition, the melting point of the modified product was 132°C. In addition, the modification amount (introduction amount) of the graft component in the maleic anhydride modified product of the copolymer of 4-methyl-1-pentene and propylene was 1.8% by mass. It should be noted that the above modification amount is obtained by 1 Measured by H-NMR measurement.

[0170] <Production of Maleic Anhydride Modified Propylene / 1-Butene Copolymer>

[0171] Production Example 5

[0172] In an autoclave (2 L capacity) fully purged with nitrogen, 900 ml of hexane and 90 g of 1-butene were added, and 1 mmol of triisobutylaluminum was added, and the temperature was raised to 70° C. Then, propylene was supplied so that the total pressure was 7 kg / cm 2 G, 0.30 mmol of methylaluminoxane and 0.001 mmol of racemic-dimethylsilylene-bis{1-(2-methyl-4-phenylindenyl)}zirconium dichloride in terms of Zr atom were added, and propylene was continuously supplied to maintain the total pressure at 7 kg / cm 2 G, while carrying out polymerization reaction for 30 minutes. After the polymerization reaction, degassing was carried out, and the polymer was recovered in a large amount of methanol and dried under reduced pressure at 110° C. for 12 hours. Thus, a propylene / 1-butene copolymer was obtained.

[0173] The weight average molecular weight of the propylene / 1-butene copolymer is 300,000. The melting point of the weight average molecular weight is 78.3° C. In addition, in the copolymer, the content ratio of the structural unit derived from propylene is 75 mol%, and the content ratio of the structural unit derived from 1-butene is 25 mol%, relative to the total amount of the structural unit derived from propylene and the structural unit derived from 1-butene. It should be noted that the above content ratio is obtained by 13 Measured by C-NMR measurement.

[0174] Next, 3 kg of propylene / 1-butene copolymer was added to 10 L of toluene, and the temperature was raised to 145° C. under a nitrogen atmosphere to dissolve the propylene / 1-butene copolymer in toluene. Further, 382 g of maleic anhydride and 175 g of di-tert-butyl peroxide as a radical polymerization initiator were supplied under stirring for 4 hours, and stirred at 145° C. for 2 hours. Thus, a maleic anhydride-modified propylene / 1-butene copolymer was obtained. Then, it was cooled, a large amount of acetone was added, and the maleic anhydride-modified propylene / 1-butene copolymer was precipitated, and then filtered, washed with acetone, and vacuum dried.

[0175] The weight average molecular weight (Mw) of the maleic anhydride-modified propylene / 1-butene copolymer was 100,000. The melting point of the maleic anhydride-modified propylene / 1-butene copolymer was 75.8°C. The amount of maleic anhydride in the maleic anhydride-modified propylene / 1-butene copolymer was 0.8% by mass. 1 Measured by H-NMR measurement.

[0176] <Production of 4-methyl-1-pentene homopolymer>

[0177] Production Example 6

[0178] 36.9 g of a powdery homopolymer of 4-methyl-1-pentene was obtained by the same procedure as in Production Example 1. However, in Production Example 6, pressurization with propylene was not performed.

[0179] The weight average molecular weight of the polymer was 337000. The weight average molecular weight / number average molecular weight (Mw / Mn) of the polymer was 2.1. The melting point of the copolymer was 222°C.

[0180] <Manufacturing of Laminated Body>

[0181] Example 1

[0182] [1st step]

[0183] As a substrate, paper is prepared.

[0184] [Step 2]

[0185] In a flask (capacity of 5 L) fully purged with nitrogen, 650 parts by mass of the copolymer of Manufacturing Example 1, 1040 parts by mass of ethyl acetate, and 1560 parts by mass of methylcyclohexane were added, and after heating to 70° C., the mixture was dissolved in 3 hours. The mixture was then cooled to below 60° C. Thus, a varnish of a coating composition was prepared. The solid content concentration of the varnish of the coating composition was 20% by mass.

[0186] [Step 3]

[0187] The varnish of the coating composition was applied to one surface of the substrate in the thickness direction and dried at 100°C for 1 minute. Thus, a heat sealant layer (film thickness after drying: 19 μm) was arranged on one surface of the substrate in the thickness direction. A laminate was produced in the above manner.

[0188] Examples 2 to 6, Comparative Examples 1, 2 and 4

[0189] The laminate was manufactured based on the same steps as in Example 1. However, the type of substrate and the composition of the varnish of the coating composition were changed according to the description in Table 1. In Example 5 and Comparative Example 2, the varnish of the coating composition was applied to one surface in the thickness direction of the substrate, left to stand at room temperature for 5 hours, and then dried at 100° C. for 1 minute.

[0190] Comparative Example 3

[0191] 60 parts by mass of the copolymer of Manufacturing Example 1 and 40 parts by mass of the propylene·ethylene random copolymer were mixed (dry blended) to obtain a mixture. Next, the mixture was put into the feed hopper of a 20 mmφ single screw extruder (single screw sheet forming machine, manufactured by Tanaka Iron Works Co., Ltd.) provided with a T die with a die lip width of 240 mm. Then, the barrel temperature was set to 230°C, the die temperature was set to 230°C, and the molten kneaded product was extruded from the T die with a thickness of 50 μm, thereby casting on one surface of the paper in the thickness direction. Thus, a laminate was manufactured.

[0192] <Evaluation>

[0193] [Breathability]

[0194] The oxygen permeability coefficient (unit: cm 3 mm / (m 2 ·24h·atm)) and carbon dioxide permeability coefficient (unit: cm 3 mm / (m 2 ·24h·atm)).

[0195] Specifically, first, the laminated body of each Example and each Comparative Example was molded into a shape of 30 mm in width×30 mm in length.

[0196] Next, according to JIS K7126-1, a differential pressure gas permeability measuring apparatus (manufactured by Toyo Seiki Seisaku-sho, Ltd.) was used to measure the laminated body under the conditions of a test temperature of 23°C and a test humidity of 0% RH with a measurement area of ​​7 cm 2The measurement was performed. For the measurement area of ​​the laminate, two aluminum masks with an adhesive made by Modern Cotrol Company with a hole of 25 mm in the center were prepared, and the sample to be measured was laminated by sandwiching the two masks, thereby adjusting. In detail, the film was arranged in a manner that the hole in the center overlapped in the two masks. The results are shown in Table 1.

[0197] [Heat sealability]

[0198] The laminate of each embodiment and each comparative example is cut into a strip of 150 mm in width and 50 mm in length, and two laminates are prepared. The two laminates are bonded together in such a way that the heat sealing layers are in contact with each other, and a heat sealing tester (thermal gradient heat sealing tester TP-701-B, manufactured by Tester Industry Co., Ltd.) is used to perform heat sealing under the conditions of a sealing width of 5 mm, 160°C, a sealing pressure of 0.3 MPa, and 2 seconds, thereby manufacturing a film. For the film, an Intesco precision testing machine (210N type (manufactured by INTESCO Co., Ltd.) is used, and under the conditions of a tensile speed of 50 mm / min and a temperature of 23°C, the film is peeled off in a direction of 180° relative to the heat sealing surface, and the peel strength (unit: N / 15mm) is measured. The test was carried out 5 times, and the average value thereof is shown in Table 1.

[0199] [Table 1]

[0200]

[0201] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, but it is only for illustration and is not to be construed as limiting. Modifications of the present invention that are obvious to those skilled in the art are included in the appended claims.

[0202] Industrial Applicability

[0203] The laminate, packaging film, and method for producing a laminate of the present invention can be suitably used in, for example, packaging materials.

Claims

1. A laminate comprising a substrate and a heat sealant layer in this order on one side in a thickness direction, The heat sealing layer is a dried product of the coating composition, The coating composition comprises a resin component, The resin component is composed of a copolymer of 4-methyl-1-pentene and an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene), and / or a modified product of the copolymer. In the copolymer, the content ratio of the structural unit derived from 4-methyl-1-pentene is 50 mol% to 99 mol% with respect to the total amount of the structural unit derived from 4-methyl-1-pentene and the structural unit derived from the α-olefin, and the content ratio of the structural unit derived from the α-olefin is 1 mol% to 50 mol%. The oxygen permeability coefficient and carbon dioxide permeability coefficient of the laminate are 1000 cm 3 mm / (m 2 ·24hr·atm) or more.

2. The laminate according to claim 1, wherein The substrate is an air-permeable porous substrate or a substrate formed of a polymer of 4-methyl-1-pentene.

3. The laminate according to claim 1, wherein The heat sealing layer has a thickness of 1 μm or more and less than 50 μm.

4. The laminate according to claim 1, wherein The peel strength measured by the following test is 2.0N / 15mm or more, Test: Two laminates were prepared; the two laminates were bonded together so that their heat-sealing layers were in contact with each other, and heat-sealed at 160°C, 0.3 MPa, and 2 seconds to produce a film; the film was peeled off in a direction of 180° relative to the heat-sealing surface at a tensile speed of 50 mm / min and a temperature of 23°C, and the peel strength was measured.

5. A packaging film comprising the laminate according to claim 1.

6. The method for producing a laminate according to claim 1, comprising the following steps: The first step is to prepare the substrate; In a second step, the coating composition is dissolved in an organic solvent to prepare a varnish; and In the third step, the varnish is applied to one surface of the substrate in the thickness direction and dried to form a heat seal layer.

Citation Information

Patent Citations

  • Resin composition containing 4-methyl-1-pentene copolymer, and film for capacitors

    CN112969726A

  • Film selectively permeable to carbon clioxidc and food packaging film comprising the same

    CN1390242A

  • Package

    JP2015189481A

  • Film and laminate film

    JP2016121322A